(Re)Defining the black body in the era of Black Lives Matter: the politics of blackness, old and new. (2nd January 2018) - Nunnally, Shayla C.
ABSTRACT: As a social construction, race has been defined differently for various racial groups. The construction of the "black body, " over time, has been fraught with societal, scientific, biological, and educational conceptualizations about the members, who comprise this group. These racial ideas have challenged the humanity, rights, and sociolegal incorporation of "black" persons into American society. In order to grapple with contemporary understandings of the "black body, " we should assess the historical discourses, public policies, and vast contexts, over time, for which the "black body" has struggled to assert its equality and liberation. Through the analysis of unconventional political contexts, such as African-American education, and particularly, historically black institutions, such as historically black colleges and universities (HBCU's) and Jim Crow black public high schools, (African)American political development can understand how race influenced the political decisions affecting the democratic experiences, agency, and responses of black Americans to their groups' racial construction and treatment. Such studies can move black sociopolitical experiences beyond historical lore and situate them within the contemporary context of Black Lives Matter's arguments, politics, and public policy interests.